2015
DOI: 10.1177/0748730415605633
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Drosophila melanogaster TRPA1 Function Affects “Siesta” Behavior but Not Synchronization to Temperature Cycles

Abstract: To maintain synchrony with the environment, circadian clocks use a wide range of cycling sensory cues that provide input to the clock (zeitgebers), including environmental temperature cycles (TCs). There is some knowledge about which clock neuronal groups are important for temperature synchronization, but we currently lack knowledge on the temperature receptors and their signaling pathways that feed temperature information to the (neuronal) clock. Since TRPA1 is a well-known thermosensor that functions in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…This serves as a second mechanism for linking changes in daytime and nighttime sleep. The sensors required for heat effects are unknown, but recent studies have suggested that both dTrpA1 and Ir25a are important in communication of temperature information to clock and activity circuits [46, 47]. …”
Section: Resultsmentioning
confidence: 99%
“…This serves as a second mechanism for linking changes in daytime and nighttime sleep. The sensors required for heat effects are unknown, but recent studies have suggested that both dTrpA1 and Ir25a are important in communication of temperature information to clock and activity circuits [46, 47]. …”
Section: Resultsmentioning
confidence: 99%
“…Because the circadian clock is entrained by light-dark and temperature cycles (Busza et al, 2007; Glaser and Stanewsky, 2005; Miyasako et al, 2007; Yoshii et al, 2010), it is possible that ambient temperature information via ACs is used for temperature entrainment. Although TRPA1 itself is neither required for temperature entrainment (Das et al, 2016; Roessingh et al, 2015) nor temperature compensation (Table 2), TRPA1 expression in TrpA1 SH -Gal4 + neurons is required for exhibiting a ‘siesta’ during temperature cycles (Das et al, 2016; Roessingh et al, 2015). Because AC neurons also integrate the temperature information from Pyx-Gal4 expressing neurons and PYX has a function in synchronizing the circadian clock to temperature cycles (Tang et al, 2013; Wolfgang et al, 2013), it is possible that AC neurons influence temperature entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep was defined as a period of inactivity of at least 5 min67. A modified version of a previously described Microsoft Excel script68 was used to measure all sleep parameters detailed in this article. Siesta sleep onset is defined as the latency of the first sleep bout and siesta offset as the end of the last sleep episode.…”
Section: Methodsmentioning
confidence: 99%